San Lorenzo and the Poggendorff illusion in Ravenna - Daneyko, Olga (Pion, 2011)
In the Mausoleum of Galla Placidia (Ravenna, Italy), the San Lorenzo lunette shows two peculiar visual effects: a transparency effect of gold seen through gold and perceptual collinearity between two parts of a cross which are physically misaligned. Both effects are found within the area of the halo surrounding the saint's head. In this work we addressed the problem posed by the physical misalignment of the cross. Our hypothesis is that the physical misalignment went unnoticed throughout history because the artist produced a perceptual alignment to correct for the Poggendorff illusion. Hence, we asked observers to align two ends of a cross in a reproduction showing the silhouette of San Lorenzo's torso holding the cross. Results support our hypothesis: both direction and magnitude of adjustments comply with the alignment in the original mosaic.